LIS Program Representatives’ Perspectives on Preparing Students for Careers in Research Data Management and Data-Related Librarianship - Abel, Jennifer; Rod, Alisa B. (Evidence Based Library and Information Practice, 2025)
Objective – This study aims to contribute a qualitative analysis of the perspectives of LIS program representatives on providing research data management (RDM) and data librarianship training opportunities to their students. The primary objectives of the study are to determine which programs currently provide training opportunities for students in RDM and related areas, as well as whether programs have provided such opportunities in the past and/or intend to do so in the future.Methods – This study incorporates in-depth qualitative empirical evidence in the form of five semi-structured interviews of representatives of Canadian LIS programs to investigate first-hand perspectives on the RDM and data-related opportunities they can provide to their students.Results – The interviews identified five major themes related to LIS programs’ RDM and data-related training offerings, including the range of formal and informal opportunities currently available in the programs; the ways in which the representatives would mentor and advise students interested in RDM or related career paths; the challenges posed by both the lack of instructors for RDM and data-related courses, and the lack of students who are interested in, or ready to pursue, data-related careers; the need for programs to develop a curriculum that meets the requirements of many stakeholders; and the effects of the rapidly changing library landscape on LIS curriculum development.Conclusion – This qualitative study sheds light on both the support that Canadian LIS programs can provide to students who are interested in RDM and data-related careers in academic libraries, and the challenges those programs face in providing that support.